Pengaruh Subtitusi Tepung Suweg (Amorphopallus campanulatus B1) Terhadap Tingkat Pengembangan, Kekerasan dan Daya Terima Bolu Suweg - Hamurwani Siwi, Hasti; Sofyan, Aan Sofyan (Journal of Food and Agricultural Product, 2022)
The average consumption of wheat flour per capita in Indonesia from 2011 to 2015 reached 13.13% and is increasing. Suweg flour has the potential to replace some wheat flour, reducing the level of consumption of wheat flour. Suweg flour has high fiber content and a low glycemic index. Sponge quality parameters can be seen from the level of development, hardness, and acceptability of the suweg sponge. This study aims to determine the effect of suweg flour substitution on the level of development, hardness, and acceptability of suweg sponge cake. The research method used was a completely randomized design with 0%, 25%, 50%, and 75% flour substitution treatments. Data analysis used One Way Anova and Kruskal-Wallis tests, then if there was an effect, continued Duncan Multiple Range Test (DMRT) with a significance level of 95%. The results showed that the highest level of development of suweg cake was in the substitution of suweg flour by 50%. The results of testing the highest hardness of suweg cake were in the substitution of suweg flour by 50%. Based on the results of the acceptability test of the overall suweg cake, panelists tended to prefer the suweg cake with suweg flour substitution by 0% with an average preference score of 5.4. Conclusion: there is no effect of suweg flour substitution on the level of development and hardness of suweg cake, but there is an effect of suweg flour substitution on the acceptability of suweg cake